Teaching Leadership in Professional Learning Communities: A Case Study From Two Public Schools in Mexico - Flores-Fahara, Manuel (2021)
This study aimed to describe the teaching leadership exercised by female teachers and principals in professional learning communities (CPA) in two public elementary schools. Naturalistic observation and conversational interviews were used under a qualitative multiple-case research approach. The development of the communities was in accordance with the organizational learning model, which includes initial organization, identification of problems, acquisition of knowledge, sharing, and use and dissemination of knowledge. The results show similarities and differences in the participation of the teachers and principals in both schools. Among the similarities, it was found that the experience helped the participants to grow and learn and that it is possible to stimulate leadership and collaboration within the framework of a professional learning community. Among the differences, the disposition of the principal was notorious. While in one of the schools, all the teachers participated, motivated by the principal, in the other school, they did not have the principal’s support, and the teachers participated spontaneously. It is possible to conclude that, in both schools, the emergence of teaching leadership was observed by giving participants a voice in their initiatives, ideas, experiences, creativity, and recognition of personal mastery. Finally, given the resistance and uncertainty that these processes generate, it is proposed that the collaboration in CPA and distributed leadership topics become the pillars of the school and be incorporated into the school culture, as well as in the initial and continuous training of teachers and principals.